Macrophage activation marker soluble CD163 may predict disease progression in hepatocellular carcinoma. (2nd January 2016) - Kazankov, Konstantin; Rode, Anthony; Simonsen, Kira; Villadsen, Gerda Elisabeth; Nicoll, Amanda; Møller, Holger Jon; Lim, Lucy; Angus, Peter; Kronborg, Ian; Arachchi, Niranjan; Gorelik, Alexandra; Liew, Danny; et al.
Abstract: Background : Tumor associated macrophages are present in hepatocellular carcinoma (HCC) and associated with a poor prognosis. The aim of the present study was to investigate the levels and dynamics of soluble (s)CD163, a specific macrophage activation marker, in patients with HCC. Methods : In a cohort from Australia, we studied 109 HCC patients, 116 patients with chronic liver disease (CLD), and 52 healthy controls. We examined associations between baseline sCD163 and parameters of HCC severity as well as overall and progression-free survival. In a cohort of 42 Danish HCC patients, we measured sCD163 at baseline and 1, 4 and 12 weeks after ablative treatment. Results : In the Australian cohort, median sCD163 was similarly increased in HCC (5.6[interquartile range 3.5–8.0] mg/L) and CLD (6.1[3.6–9.6] mg/L) patients as compared to controls (2.0[1.5–2.7] mg/L, p < 0.001). sCD163 correlated with Child-Pugh and MELD scores in both HCC and CLD patients. Patients with high sCD163 levels had shorter progression-free survival ( p < 0.001), but not overall survival ( p = 0.15). In the Danish cohort, patients with HCC progression at 12 weeks had an increase in sCD163. There was no association between sCD163 and HCC size, number, vascular invasion or metastasis in any of the cohorts. Conclusions : We confirmed increased sCD163 levels in CLD and HCC patients associated with Child-Pugh and MELD scores and portal hypertension, but not with HCC size and number, or metastasis. As a novel finding, baseline sCD163 appeared to predict a rapid HCC progression, as sCD163 increased during follow-up in HCC patients who showed progression.